James Podgers, Retired ABA Journal Editor, Dies at 67 - Weiss, Debra Cassens (ABA journal, 2018)
Funeral services took place in February for James Podgers, 67, a retired ABA Journal editor known for his deep knowledge of the American Bar Association and its inner workings. "Jim was the picture of a classic Chicago journalist," says Molly McDonough, ABA Journal editor and publisher. In a bereavement notice to ABA staffers, Reginald Davis, Journal managing editor, noted that Podgers was known for his "cogent questions" at the end of staffwide information sessions known as town hall meetings.